Cross array electrocatalyst as well as preparation method and application thereof
By forming a cross-supported nanosheet array structure in the electrocatalyst, the problem of low oxygen evolution activity and stability of the existing electrocatalyst is solved, and efficient electrocatalytic oxygen evolution performance and long-term stable operation are achieved, with industrial applications potential.
Patent Information
- Application Number
- CN202411682796.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-07
AI Technical Summary
Existing electrocatalysts have low performance in oxygen evolution activity and stability, and it is difficult to meet the needs of efficient electrolytic water decomposition reactions.
The corrosion-treated nickel mesh is placed in a specially made corrosion solution for reaction, and a cross-array electrocatalyst with a cross-supported nanosheet array structure is formed. The method includes hydrochloric acid corrosion and ethylene glycol as corrosion solvents to form a reinforced bond and optimize the reaction environment.
It realizes efficient electrocatalytic oxygen evolution activity and stability, drives high current density only with low overpotential, and operates stably for more than 4500 hours under industrial-grade conditions, with industrial application prospects.
Smart Images

Figure CN119392285A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field related to electrocatalysts, and more specifically, relates to a cross-array electrocatalyst and a preparation method and application thereof. Background Art
[0002] The rapid development of today's society is inseparable from various carbon-based fossil energy sources. Fossil fuels, mainly coal, oil and natural gas, have become the key cornerstones of economic and social development. However, the non-renewable nature of fossil energy means that it is bound to be exhausted, and fossil energy will release a large amount of carbon emissions during its use, causing an indelible impact on the earth's ecological environment. It is urgent to find a renewable clean energy that can replace traditional fossil fuels.
[0003] Among renewable energy sources, hydrogen is an excellent fuel due to its high energy density. In addition, hydrogen produces water after combustion, which is harmless to the environment, so it has attracted widespread attention. At present, "grey hydrogen" and "blue hydrogen" produced by fossil fuel combustion and reforming account for the majority of hydrogen production. "Green hydrogen" produced by electrolysis of water based on renewable energy has a very broad development prospect. In the electrolysis of water hydrogen production technology, water molecules react on the surface of the catalyst under the drive of an applied voltage by using a suitable catalyst to break and reorganize chemical bonds, produce hydrogen at the cathode, and produce oxygen at the anode. However, due to the four-electron transfer process of the anode oxygen evolution reaction, its reaction kinetics are very slow. The electrolysis of water decomposition reaction as a whole needs to overcome the theoretical voltage of 1.23V. Therefore, designing efficient electrocatalysts to promote the water decomposition reaction is the key to the electrolysis of water hydrogen production technology. Precious metal-based catalysts mainly composed of platinum, iridium, and ruthenium have excellent electrocatalytic properties and have attracted widespread attention. However, due to the low content of precious metals in the earth's crust and their high prices, it is difficult to achieve large-scale application, and it is urgent to develop high-performance non-precious metal-based electrocatalysts. At present, the most mature technology for industrial application, alkaline solution electrolysis of water to produce hydrogen, uses nickel mesh as a bifunctional catalyst. However, the electrocatalytic oxygen evolution reaction activity of nickel mesh is low, and a high voltage is required to drive water decomposition. The high electricity cost restricts the development of alkaline solution electrolysis technology.
[0004] Previous studies usually used powder catalysts and loaded the catalysts on a carrier by spraying or other methods. This method usually requires the use of conductive agents, polymer binders, etc. The introduction of additional substances will affect the performance of the catalyst itself, resulting in limited release of catalyst performance. In addition, the physical adsorption effect between the catalyst prepared in this way and the carrier is weak, and its mechanical stability is unreliable. Summary of the invention
[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a cross-array electrocatalyst and a preparation method and application thereof, which aims to solve the problems of low oxygen evolution activity and stability of existing catalysts.
[0006] To achieve the above object, according to one aspect of the present invention, a method for preparing a cross-array electrocatalyst is provided, the preparation method comprising the following steps:
[0007] The nickel mesh after corrosion treatment is placed in a corrosion solution and kept warm for a predetermined reaction time to obtain a cross-array electrocatalyst, wherein the electrocatalyst forms a nanosheet array structure that crosses and supports each other; wherein the nickel mesh is corroded with hydrochloric acid; the corrosion solution is obtained by dissolving sodium thiosulfate pentahydrate, nickel chloride hexahydrate, ferrous chloride tetrahydrate and sodium orthovanadate in ethylene glycol.
[0008] Further, Na2S2O3·5H2O, NiCl2·6H2O, FeCl2·4H2O and Na3VO4 powder are placed in ethylene glycol solvent and stirred evenly with a magnetic stirrer to obtain the corrosion solution.
[0009] Furthermore, the nickel mesh is taken out after the reaction is completed, and the corrosion solution is cleaned with deionized water and dried to obtain a cross-array electrocatalyst material.
[0010] Furthermore, the mass of Na2S2O3·5H2O powder is 0.1g~10.0g; the mass of NiCl2·6H2O powder is 0.01g~1.0g; the mass of FeCl2·4H2O powder is 0.05g~5.0g; the mass of Na3VO4 powder is 0.02g~2.0g; the amount of ethylene glycol used is 20mL~500mL; and the magnetic stirring speed is 200rpm~800rpm.
[0011] Furthermore, the magnetic stirring speed is 200 rpm to 800 rpm.
[0012] Furthermore, the reaction temperature is 60°C to 140°C, the reaction time is 15min to 12h, and the heating method is oil bath heating.
[0013] Furthermore, the concentration of the hydrochloric acid solution is 1 mol L -1 ~5mol L -1 The hydrochloric acid etching time is 10min~120min.
[0014] Furthermore, the drying method is to place the product in a vacuum drying oven, set the drying temperature to 20° C. to 60° C., and the drying time to 1 h to 24 h.
[0015] The present invention also provides a cross-array electrocatalyst, which is prepared by the cross-array electrocatalyst preparation method as described above, and has a mutually cross-supported nanosheet array structure grown on a nickel mesh substrate, wherein the length of the nanosheet is 10nm to 50nm and the thickness is to 2nm.
[0016] The present invention also provides an application of the cross-array electrocatalyst as described above or a cross-array electrocatalyst prepared by the preparation method of the cross-array electrocatalyst as described above in hydrogen production by electrolysis of water.
[0017] In general, compared with the prior art, the cross-array electrocatalyst and its preparation method and application provided by the present invention have the following beneficial effects:
[0018] 1. The nickel mesh after corrosion treatment is placed in a corrosion solution for a predetermined time to keep warm and react, thereby obtaining a cross-array electrocatalyst. The catalyst prepared by the present invention has a nanosheet array structure that crosses and supports each other. The special structure enables it to construct an ion confined space, which is beneficial to the adsorption and enrichment of reactants on the catalyst interface, constructs a localized reactant-rich environment, and exhibits excellent electrocatalytic oxygen evolution activity.
[0019] 2. The nickel mesh substrate is etched with hydrochloric acid solution to clean the surface oxidized inert layer, which is conducive to the formation of strong chemical bonds between the nanosheets grown on the nickel mesh and the nickel mesh substrate, thereby enhancing the electron transfer efficiency during the electrocatalytic process. At the same time, the uneven and rough surface of the nickel mesh after hydrochloric acid etching is conducive to providing more nucleation sites.
[0020] 3. Using ethylene glycol as the corrosion solvent, the boiling point of ethylene glycol is 197°C. Compared with water as the solvent, it can accept a higher reaction temperature and provide more energy for nucleation growth.
[0021] 4. By using chemical corrosion as the reaction method, the synthesized electrocatalyst can be prepared in a controllable manner through the corrosion solution ratio, reaction temperature, and reaction time, thereby improving and optimizing its oxygen evolution activity and stability.
[0022] 5. The catalyst prepared by the preparation method provided by the present invention has excellent electrocatalytic oxygen evolution activity in an alkaline environment. The prepared catalyst only needs an overpotential of 200mV, 298mV, and 350mV to drive 10mA cm -2 、400mAcm -2 , 1000mA cm -2 of current density.
[0023] 6. The catalyst prepared by the preparation method provided by the present invention has excellent electrocatalytic oxygen evolution stability, which is specifically manifested in that: the prepared catalyst presents a mutually cross-supported nanosheet structure, has mechanical support stability, and the formed three-dimensional pore structure is conducive to the smooth outflow of bubbles, thereby reducing the impact force of bubbles; the prepared catalyst is at 400mA cm -2It can run stably for more than 4500 hours at industrial-grade high current density without showing obvious performance degradation.
[0024] 7. The preparation method adopted by the present invention does not require pressurization, has mild conditions, low cost, is easy to prepare and synthesize on a large scale, and has industrial application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 a and b are respectively a scanning electron microscope image and an energy dispersion image of an electrocatalyst prepared by a method for preparing a cross-array electrocatalyst provided by the present invention;
[0026] Figure 2 This is a perspective electron microscope image of the cross-array electrocatalyst prepared by the present invention after being sliced perpendicular to the surface of the nickel mesh;
[0027] Figure 3 is a Raman spectrum of the cross-array electrocatalyst prepared by the present invention;
[0028] Figure 4 It is a linear sweep voltammetric curve of the cross-array electrocatalyst prepared by the present invention after compensation in 1M KOH electrolyte;
[0029] Figure 5 The cross-array electrocatalyst prepared by the present invention is in 1M KOH electrolyte at 400mA cm -2 Voltage-time curves at constant current density. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0031] The present invention provides a method for preparing a cross-array electrocatalyst. The cross-array electrocatalyst prepared by the preparation method has a mutually cross-supported nanosheet array structure, which can construct an ion confinement space, is conducive to the adsorption and enrichment of reactants on the catalyst interface, constructs a local reactant-rich environment, exhibits excellent electrocatalytic oxygen evolution activity, and only requires an overpotential of 200mV, 298mV, or 350mV to drive 10mA cm -2 , 400mA cm -2 , 1000mA cm -2The mechanical support and three-dimensional pore structure of the electrocatalyst give it excellent bubble impact bearing capacity, making it have excellent electrocatalytic oxygen evolution stability at 400mA cm -2 It can run stably for over 4500 hours under industrial-grade high current and has the prospect of industrial application.
[0032] The preparation method mainly comprises the following steps: placing the nickel mesh after corrosion treatment in a corrosion solution for a predetermined time to keep the temperature and react, thereby obtaining a cross-array electrocatalyst, wherein the electrocatalyst forms a nanosheet array structure that crosses and supports each other; wherein the nickel mesh is corroded by hydrochloric acid; and the corrosion solution is obtained by dissolving sodium thiosulfate pentahydrate, nickel chloride hexahydrate, ferrous chloride tetrahydrate and sodium orthovanadate in ethylene glycol.
[0033] In a specific embodiment, the steps of the preparation method are:
[0034] Pretreatment of the nickel mesh: the nickel mesh is cut into a predetermined size, ultrasonically washed with anhydrous ethanol and deionized water, then surface-etched with a hydrochloric acid solution, and then cleaned and dried for later use.
[0035] Preparation of corrosion solution: Commercial Na2S2O3·5H2O, NiCl2·6H2O and FeCl2·4H2O as well as Na3VO4 powder were placed in ethylene glycol solvent and stirred evenly with a magnetic stirrer to obtain a corrosion solution.
[0036] Synthesis of electrocatalyst: Place the pretreated nickel mesh into the corrosion solution and keep it warm at a predetermined reaction temperature for reaction.
[0037] Post-treatment of the electrocatalyst: After the reaction is completed, the nickel mesh is taken out, the corrosion solution is cleaned with deionized water, and then dried to obtain the cross-array anode electrocatalyst material.
[0038] The ultrasonic washing time is 10 min to 60 min; the concentration of the hydrochloric acid solution is 1 mol L -1 ~5mol L -1, the hydrochloric acid etching time is 10min~120min; the cleaning method is to rinse with deionized water 3~5 times; the drying method is to put it into a vacuum drying oven, set the drying temperature to 20℃~60℃, and the drying time is 1h~24h; the mass of commercial Na2S2O3·5H2O powder is 0.1g~10.0g; the mass of commercial NiCl2·6H2O powder is 0.01g~1.0g; the mass of commercial FeCl2·4H2O powder is 0.05g~5.0g; the mass of commercial Na3VO4 powder is 0.02g~2.0g; the amount of ethylene glycol is 20mL~500mL; the magnetic stirring speed is 200rpm~800rpm; the reaction temperature is 60℃~140℃, the reaction time is 15min~12h, and the insulation method is oil bath heating.
[0039] The present invention also provides a cross-array electrocatalyst, which is prepared by the cross-array electrocatalyst preparation method as described above, and has a dense and uniform mutually cross-supported nanosheet array structure grown on a nickel mesh substrate, wherein the length of the nanosheet is 10nm to 50nm and the thickness is to 2nm.
[0040] During the pretreatment of the nickel mesh, etching the nickel mesh substrate with a hydrochloric acid solution can clean the surface oxidized inert layer, which is conducive to the formation of a strong chemical bond between the nanosheets grown on the nickel mesh and the substrate, and enhances the electron transfer efficiency during its electrocatalytic oxygen evolution. At the same time, the uneven rough surface of the nickel mesh after hydrochloric acid etching is conducive to providing more nucleation sites. Ethylene glycol can accept a higher reaction temperature than water as a solvent, providing more energy for nucleation growth. Using chemical corrosion as a reaction method, the synthesized electrocatalyst can be prepared in a controllable manner through the ratio of the corrosion solution, the reaction temperature, and the reaction time, thereby improving and optimizing its oxygen evolution activity and stability. The preparation method does not require pressurization, the conditions are mild, the cost is low, and it is easy to prepare and synthesize on a large scale, which has prospects for industrial application.
[0041] The cross-array electrocatalyst prepared by the present invention has excellent electrocatalytic oxygen evolution activity due to its unique cross-supported nanosheet array structure, which is conducive to the adsorption and enrichment of reactants at the catalyst interface and constructs a localized reactant-rich environment. Its mechanical support and three-dimensional pore structure give it excellent bubble impact bearing capacity, so that it has excellent electrocatalytic oxygen evolution stability.
[0042] The present invention also provides an application of the cross-array electrocatalyst as described above in hydrogen production by electrolysis of water.
[0043] The present invention is further described in detail below with reference to specific embodiments.
[0044] Example 1
[0045] The steps of the method for preparing the cross-array electrocatalyst provided in Example 1 of the present invention are as follows:
[0046] Cut the nickel mesh into 1×3cm 2 , size, were soaked in 50 mL of anhydrous ethanol and deionized water respectively and placed in an ultrasonic cleaner for 10 min. The cleaned nickel mesh was placed in a 3 mol L -1 The sample was etched in a hydrochloric acid solution for 60 min, then rinsed with deionized water for 5 times, placed in a vacuum drying oven, set the temperature to 40 °C, and dried for 1 h.
[0047] Accurately weigh 0.9927 g of commercial Na2S2O3·5H2O powder, 0.1188 g of commercial NiCl2·6H2O powder, 0.4970 g of commercial FeCl2·4H2O powder, and 0.3678 g of commercial Na3VO4 powder, add them to 20 mL of ethylene glycol, add a magnet, use a magnetic stirrer to dissolve them, set the speed to 400 rpm, and obtain a corrosion solution.
[0048] Put the dried nickel mesh into the corrosion solution, put the nickel mesh and the corrosion solution into an oil bath, set the reaction temperature to 120°C, and the reaction time to 30 minutes. After the reaction is completed, take out the nickel mesh. It can be seen that the surface of the originally silvery white nickel mesh turns brown-black, and a cross-array anode electrocatalyst is obtained.
[0049] The cross-array electrocatalyst prepared in this example was observed using a scanning electron microscope. Figure 1 As shown in a in the figure, a layer of mutually cross-supported nanosheet array structure grows uniformly and densely on the surface of the nickel mesh, where the nanosheets are very small, with a length of 10nm to 50nm and a thickness of ~2nm. The extremely small scale means a huge specific surface area, which can expose multiple reactive active sites. Figure 1 Figure b shows the energy dispersion diagram of the nickel-based interwoven nanosheet array electrocatalyst, showing the uniform distribution of Ni, Fe, V, and S elements.
[0050] The surface of the nickel mesh was further cut vertically using a double-beam scanning electron microscope to obtain a vertical cross section of the electrocatalyst, which was then observed using a transmission electron microscope. Figure 2 As shown, it can be seen that the material layer has a large number of clear white lines that cross-link and support each other, that is, the cross-sectional structure of the nanosheets, which proves the successful synthesis of the cross-array structure. The cross-supported nanosheet structure can provide excellent mechanical support, and its three-dimensional pore structure can facilitate the removal of bubbles.
[0051] Raman spectroscopy was performed to characterize the prepared cross-array electrocatalysts, e.g. Figure 3 As shown, at 480cm -1A broad peak appears near the wave number, corresponding to the Ni-OH signal peak, indicating that the prepared cross-array electrocatalyst material is nickel-based hydroxide. Combined with the element energy dispersion diagram, Fe, V and S elements are evenly distributed in it, and it can be further known that the prepared cross-array electrocatalyst is nickel-based hydroxide doped with Fe, V and S elements.
[0052] In order to verify that the cross-array electrocatalyst prepared in this example has excellent electrocatalytic oxygen evolution activity, it was cut into 1×1.5 cm 2 , fixed with a platinum electrode clip and wrapped with sealing glue, exposing 1×1cm 2 As the effective reaction area, this was used as the working electrode. This working electrode was used together with a standard Ag / AgCl electrode as the reference electrode and a carbon rod as the counter electrode. 80 mL of 1 mol L -1 KOH was used as the electrolyte to form a standard three-electrode test system. The Autolab PGSTAT 302N electrochemical workstation was connected as a DC output power supply to perform the electrocatalytic oxygen evolution performance test. The compensated linear sweep voltammetric curve is shown in Figure 4 As shown in Figure 2, it can be seen that the prepared cross-array electrocatalyst only requires 200 mV, 298 mV, and 350 mV overpotentials to drive 10 mA cm -2 , 400mA cm -2 , 1000mA cm -2 In addition, using the same standard three-electrode system, at 400 mA cm -2 The stability test was carried out at a current density of Figure 5 As shown, the prepared cross-array electrocatalyst has a high conductivity at 400 mA cm -2 It operated stably for more than 4500 hours at industrial-grade high current density without showing obvious performance degradation. It has excellent electrocatalytic oxygen evolution activity and stability and has development prospects for industrial applications.
[0053] Example 2
[0054] The steps of the method for preparing the cross-array electrocatalyst provided in Example 2 of the present invention are as follows:
[0055] Cut the nickel mesh into 1×3cm 2 , size, were soaked in 400 mL of anhydrous ethanol and deionized water respectively and placed in an ultrasonic cleaner for 50 min. The cleaned nickel mesh was placed in a 4 mol L -1 The sample was etched in a hydrochloric acid solution for 100 min, then rinsed with deionized water 4 times, placed in a vacuum drying oven, set the temperature to 50 °C, and dried for 15 h.
[0056] Accurately weigh 5 g of commercial Na2S2O3·5H2O powder, 0.6 g of commercial NiCl2·6H2O powder, 4 g of commercial FeCl2·4H2O powder, and 1.5 g of commercial Na3VO4 powder, add them to 400 mL of ethylene glycol, add a magnet, use a magnetic stirrer to dissolve them, set the speed to 500 rpm, and obtain a corrosion solution.
[0057] Put the dried nickel mesh into the corrosion solution, put the nickel mesh and the corrosion solution into an oil bath, set the reaction temperature to 80°C, and the reaction time to 10 hours. After the reaction is completed, take out the nickel mesh. It can be seen that the surface of the originally silvery white nickel mesh has turned brown-black, and a cross-array anode electrocatalyst is obtained.
[0058] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a cross-array electrocatalyst, characterized in that: The preparation method comprises the following steps: The nickel mesh after corrosion treatment is placed in a corrosion solution and kept warm for a predetermined reaction time to obtain a cross-array electrocatalyst, wherein the electrocatalyst forms a nanosheet array structure that crosses and supports each other; wherein the nickel mesh is corroded with hydrochloric acid; the corrosion solution is obtained by dissolving sodium thiosulfate pentahydrate, nickel chloride hexahydrate, ferrous chloride tetrahydrate and sodium orthovanadate in ethylene glycol.
2. The method for preparing a cross-array electrocatalyst according to claim 1, characterized in that: Na2S2O3·5H2O, NiCl2·6H2O, FeCl2·4H2O and Na3VO4 powder are placed in ethylene glycol solvent and stirred evenly with a magnetic stirrer to obtain the corrosion solution.
3. The method for preparing a cross-array electrocatalyst according to claim 2, characterized in that: After the reaction is completed, the nickel mesh is taken out, the corrosion solution is cleaned with deionized water and dried to obtain a cross-array electrocatalyst material.
4. The method for preparing a cross-array electrocatalyst according to claim 2, characterized in that: The mass of Na2S2O3·5H2O powder is 0.1g~10.0g; the mass of NiCl2·6H2O powder is 0.01g~1.0g; the mass of FeCl2·4H2O powder is 0.05g~5.0g; the mass of Na3VO4 powder is 0.02g~2.0g; the amount of ethylene glycol used is 20mL~500mL; and the magnetic stirring speed is 200rpm~800rpm.
5. The method for preparing a cross-array electrocatalyst according to claim 2, characterized in that: The magnetic stirring speed is 200 rpm to 800 rpm.
6. The method for preparing a cross-array electrocatalyst according to any one of claims 1 to 5, characterized in that: The reaction temperature is 60°C to 140°C, the reaction time is 15min to 12h, and the heat preservation method is oil bath heating.
7. The method for preparing a cross-array electrocatalyst according to claim 1, characterized in that: The concentration of hydrochloric acid solution is 1 mol L -1 ~5mol L -1 The hydrochloric acid etching time is 10min~120min.
8. The method for preparing a cross-array electrocatalyst according to claim 3, characterized in that: The drying method is to place it in a vacuum drying oven, set the drying temperature to 20°C ~ 60°C, and the drying time to 1h ~ 24h.
9. A cross-array electrocatalyst, characterized in that: The cross-array electrocatalyst is prepared by the preparation method of the cross-array electrocatalyst described in any one of claims 1-8, and a mutually cross-supported nanosheet array structure is grown on the nickel mesh substrate, and the length of the nanosheet is 10nm to 50nm and the thickness is 2nm.
10. Use of the cross-array electrocatalyst according to claim 9 or the cross-array electrocatalyst prepared by the preparation method of the cross-array electrocatalyst according to any one of claims 1 to 8 in hydrogen production by electrolysis of water.
Citation Information
Cited By
Preparation method of manganese-doped nickel sulfide / porous foamed nickel electrode for bifunctional alkaline electrolytic water
CN120138693A
A preparation method of a bifunctional alkaline electrolytic water manganese-doped nickel sulfide / porous nickel foam electrode
CN120138693B